Implementasi Pendidikan Sufistik Dengan Konsep Ma’rifat Syekh Siti Jenar Dalam Pendidikan Karakter Siswa - Muslikhatun Nadiyah (Universitas Wahid Hasyim Semarang, 2021)
This article is a summary of the literature research on the Manunggaling Kawulo-Gusti Concept Book in Higher Education Management written by Mahmutarom HR. This book discusses a leader who can protect and protect his subordinates by using the concept of Sufism Shaykh Siti Jenar, namely Manunggaling Kawulo-Gusti, which can be interpreted as a single leader (gusti) with kawulo (people) who egalitarian has the same position, only roles, tasks , and just a different function. Manunggaling Kawulo Gusti is only a dialectic, that the unity of leadership must be vertical as well as horizontal. The study of this book uses content analysis relating to Sufism education. The concept has similarities with the teachings of Sufism including Ibn Arabi, Al Ghazali and others. The concept of sufistic education is finally brought to be applied in character education for students. Because seeing from the conditions of the times that the moral crisis is increasingly rooted in society. To overcome this, sufistic education is very much needed besides spiritual education. Keywords: Manunggaling Kawulo Gusti, Sufisic Education, Character Education Of Students